2003
DOI: 10.1590/s0100-204x2003000700002
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura do solo e acumulação de nutrientes pelo amendoim forrageiro

Abstract: Resumo -O objetivo deste trabalho foi determinar as taxas de cobertura do solo, produção de biomassa e acumulação total de N, P e K da parte aérea da leguminosa herbácea perene amendoim forrageiro (Arachis pintoi Krapov. & W.C. Greg.), em diferentes densidades e espaçamentos de plantio. O delineamento experimental adotado foi de blocos ao acaso, em arranjo fatorial 2x4, com quatro repetições. Os tratamentos constaram de espaçamentos entre sulcos de plantio (25 e 50 cm), e de densidades de plantas (2, 4, 8 e 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
19

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 8 publications
3
17
0
19
Order By: Relevance
“…Perin et al (2003) confirmed that C. juncea was able to incorporate 89 kg ha -¹ of N into the soil via BNF, when associated with millet, and under experimental conditions C. juncea had the highest growth competitiveness with millet, due to the higher biomass production, about 31% higher than millet. Heinrichs and Fancelli (1999) found no difference in the levels of nitrogen when the vetch leguminous was associated with oats, regardless of proportion.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Perin et al (2003) confirmed that C. juncea was able to incorporate 89 kg ha -¹ of N into the soil via BNF, when associated with millet, and under experimental conditions C. juncea had the highest growth competitiveness with millet, due to the higher biomass production, about 31% higher than millet. Heinrichs and Fancelli (1999) found no difference in the levels of nitrogen when the vetch leguminous was associated with oats, regardless of proportion.…”
Section: Resultssupporting
confidence: 64%
“…However, for providing low dry matter with composition of low C:N ratio and loads of soluble compounds, it shows rapid decomposition and mineralization (Zotarelli, 2000), and therefore it does not allow adequate coverage and soil protection. However, there is larger N input in the system with the introduction of this leguminous by biological nitrogen fixation (BNF) (Perin et al, 2003) and there are no reports to Cerrado region regarding the reduction of nitrogen fertilization being possible in the cotton in subsequent cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…The N amount in the dry biomass was much lower than reported by Soares et al (2006). A. pintoi can produce 20 Mg ha -1 of biomass per year and accumulate 520 kg ha -1 N (Perin et al, 2003). S. guianensis and C. mucunoides contained intermediate amounts of nutrients.…”
Section: Nutrients In Green Manure Biomassmentioning
confidence: 99%
“…Other factors are the amount and quality of the residue produced, the nutrient amount released through residue decomposition, and the temporary synchrony between the nutrient release by decomposition and crop requirements. Among the many legume species used as green manure, Stizolobium aterrimum, Arachis pintoi, Calopogonium mucunoides and Stylosanthes guianensis stand out owing to the ability to produce high amounts of biomass and to accumulate high nutrient concentrations, even in soils with low natural fertility and high acidity, besides the atmospheric N 2 fixation capacity (Aita et al, 2000;Niang et al, 2002;Muhr et al, 2002;Borkert et al, 2003;Perin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic considerably increases the economic return of the main activity considerably, besides reducing the application of the conventional chemical fertilizers. Species from this botanical family also present rapid decomposition compared to other families (PERIN et al, 2003). This happens because these plants present low relation between carbon and nitrogen (C/N ratio) to .…”
Section: Introductionmentioning
confidence: 97%